Intervention method in the reduction the accidentability index in the Aesa mining cntractor - López Montalbán, Manuel Enrique (2020)
The implementation of the intervention method reduces the accident rate in the AESA mining contractor and contributes to the creation of a safety culture in both the worker and the company. Security has been improved in many aspects. Now, there are security norms, procedures, formats, standards, security methodologies based on the behavior of people, incidents and other events generated by nature and rock. There are also immediate response programs for emergencies that arise. The influence of the intervention method in reducing the accident rate has been highly positive since workers have been informed and trained in safety issues by implementing this method; The safety culture has improved, since now 87.5% of the participants know what job safety is, staff turnover has improved considerably since workers previously did not know the benefits of having life insurance, to stay safer in their workplace and avoid staff turnover, the reduction in the frequency of disabling accidents has been considerably since workers have been trained using the method on the benefits offered by IPERC for the identification of hazards and assess risks to qualify them according to the dangerousness.